2018
DOI: 10.1016/j.marpolbul.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The true depth of the Mediterranean plastic problem: Extreme microplastic pollution on marine turtle nesting beaches in Cyprus

Abstract: A B S T R A C TWe sampled 17 nesting sites for loggerhead (Caretta caretta) and green turtles (Chelonia mydas) in Cyprus. Microplastics (< 5 mm) were found at all locations and depths, with particularly high abundance in superficial sand. The top 2 cm of sand presented grand mean ± SD particle counts of 45,497 ± 11,456 particles m −3 (range 637-131,939 particles m −3 ). The most polluted beaches were among the worst thus far recorded, presenting levels approaching those previously recorded in Guangdong, South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 64 publications
1
34
1
Order By: Relevance
“…Beach survey is regarded as the simplest and most cost- effective method to provide a reasonable proxy for marine debris environmental availability 58 . The beaches of N Cyprus display a high burden of marine source and low land-based input of plastic debris due to the current and wind patterns around the coastline in addition to low population and human visitation to the beaches 59 . Cyprus is situated in the Levantine Basin with minimal interaction with the western Mediterranean.…”
Section: Methodsmentioning
confidence: 99%
“…Beach survey is regarded as the simplest and most cost- effective method to provide a reasonable proxy for marine debris environmental availability 58 . The beaches of N Cyprus display a high burden of marine source and low land-based input of plastic debris due to the current and wind patterns around the coastline in addition to low population and human visitation to the beaches 59 . Cyprus is situated in the Levantine Basin with minimal interaction with the western Mediterranean.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we have shown that synthetic particles including microplastics (<5 mm) were present in every turtle, across all species and ocean ysis here but ingestion may be generally higher in the MED basin than the wider ATL or PAC. Global models predict some of the world's highest concentrations of marine plastics in this basin (Cózar et al, 2014;Duncan et al, 2018;Eriksen et al, 2014;Suaria et al, 2016). Further, more exhaustive sampling is required to fully appraise interspecific and geographic differences.…”
Section: Synthetic Particle Ingestion In Marine Turtlesmentioning
confidence: 99%
“…The number of plastic particles found in the feces of the turtles involved in our study can be considered as quite high, with respect to data generally reported for the gastrointestinal content of dead stranded turtles. For instance, Duncan et al (2018) found an average plastic micro-particles content ranging between 10 and 15 per 100 ml of gastric content of both C. caretta and Chelonia mydas from the Mediterranean Sea. Such number, even if higher than those reported for the same species of turtles recovered from Atlantic and Pacific oceans in the same paper, is still very low in comparison to the PD counts reported in our work, normalized to 10 g of solid feces.…”
Section: Discussionmentioning
confidence: 99%